Forster resonant energy transfer in QD structures - Bradley, Louise (My University, 2009)
Forster resonant energy transfer (FRET) has been investigated in two different quantum dot (QD) structures. Colloidal CdTe QDs of two different sizes act as energy donors and acceptors. They have been deposited in a mixed monolayer and a separate donor/acceptor layer structure. The optical properties of these structures have been analysed by steady-state absorption and photoluminescence (PL) spectroscopy, as well as time-resolved PL measurements. To characterize FRET in the mixed QD monolayer, a theory of FRET in two dimensions, taking into account exclusion zones around the donors, has been applied. This theory allows for the extraction of all important FRET parameters from time-resolved donor PL measurements only and also explains the acceptor concentration dependence of the FRET efficiency in the mixed QD layer. In a separate donor/acceptor layer structure the characteristic distance dependence of the FRET process has been demonstrated and the increase of the FRET efficiency with increasing acceptor concentration has been observed.
Proceedings of 11th International Conference on Transparent Optical Networks
11th International Conference on Transparent Optical Networks
PUBLISHED
Azores
Keywords: Forster resonant energy transfer (FRET); Nanoscience & Materials